Becoming economically independent - Civardi, Marisa (Metodološki zvezki, 2007)
This paper analyses patterns of behaviours of about three thousand graduates in some northern and central Italian universities. Different approaches to the job market and/or to further qualifications are followed up during the year after graduation and are related both to some choices adopted previously at university and to family traits, by means of longitudinal methods of Event History Analysis (EHA). Apparent behavioural inertia from college to postgraduate period reveals a commonly shared underlying attitude. Also, family influence seems well conveyed by parents' educational levels, which emphasize the mothers' role in improving graduates qualifications and the fathers' function in involving their children in self employment.
Keywords: diplomanti; podiplomski študij; trg dela; zaposlovanje; družina; family; ekonomska neodvisnost; osamosvojitev; Italija; Italy; raziskave